Phase evolution and characterization of mechanically alloyed hexanary Al16.6Mg16.6Ni16.6Cr16.6Ti16.6Mn16.6 high entropy alloy. Issue 4 (July 2020) - Parameswaran, P.; Rameshbabu, A.M.; Vijayan, V.; Sathish Kumar, G.; Sakthivel, C.; Pargunam, N.; Godwin Antony, A.
Abstract : The design, processing, phase generation, microstructure, mechanical properties and homogeneity of Hexanary (Al16.6 Mg16.6 Ni16.6 Cr16.6 Ti16.6 Mn16.6 ) High Entropy Alloy (HEA) were analyzed. The trial and error method was used to establish the composition (in atomic percentage) of the hexanary alloy. The alloy was prepared through Mechanical Alloying (MA) and Spark Plasma Sintering (SPS). The phase formed after the MA process has BCC solid solution with crystal size less than 10 nm. The stability of the alloy as analyzed using Thermo-Gravimetric Analysis (TGA) and found that the alloy was stable upto 850 °C. The SPS was done for the MA samples at 850 °C with 50 MPa pressure and its density was found to be 98.83%. The phase after SPS were evaluated with crystal structure of FCC dispersed in the BCC structure. The homogeneity of the composition was deep-rooted by Energy Dispersive Spectroscopy (EDS). The hardness of the alloy is found to be 680 ± 20 HV. The progression of the phase imply that this alloy is pertinent for both high strength and high temperature applications.